2022
DOI: 10.22303/melt.7.1.2022.36-45
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climbing Grammar Mountain Game on Students’ Lexicogrammatical Features of Personal Recount Text Mastery (A Study at The Eigth Grade Students of MTS YPKS Padangsidimpuan In 2021/2022 Academic Year)

Abstract: The purpose of this research was to found out: 1) The application of Climbing Grammar Mountain Game on Students ' Lexicogrammatical Features of Personal Recount Text Mastery,2) The Students' Lexicogrammatical Features of Personal Recount Text Mastery before and after using Climbing Grammar Mountain Game, 3) Whether there is any significant effect of Climbing Grammar Mountain Game on Lexicogrammatical Features of Personal Recount Text Mastery at the Eighth Grade Students of MTs YPKS Padangsidimpuan.This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several recent research studies have also demonstrated the effectiveness of using the Climbing Grammar Mountain Game in English education. The climbing grammar mountain game has a significant influence on the lexicogrammatically parts of personal recall text learning of eighth-grade pupils in one of Padangsidimpuan's private Islamic schools, according to Sihombing et al (2022). Pangesti et al (2021) demonstrated the effectiveness of utilising a game to teach the Simple Past Tense.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent research studies have also demonstrated the effectiveness of using the Climbing Grammar Mountain Game in English education. The climbing grammar mountain game has a significant influence on the lexicogrammatically parts of personal recall text learning of eighth-grade pupils in one of Padangsidimpuan's private Islamic schools, according to Sihombing et al (2022). Pangesti et al (2021) demonstrated the effectiveness of utilising a game to teach the Simple Past Tense.…”
Section: Introductionmentioning
confidence: 99%